A massive, energetic model for the luminous transitional Type Ib/IIb SN 2020cpg. Issue 4 (27th October 2022) - Teffs, J; Mazzali, P A; Medler, K; Hachinger, S
ABSTRACT: Using a combined spectral and light-curve modelling approach, we fit a massive and energetic explosion model to the luminous Type Ib/IIb SN 2020cpg. This model has an ejected mass of ∼(7 ± 2) M⊙ with a final explosion energy of ∼(6 ± 1) × 10 51  erg with M Ni  = 0.27 ± 0.05 M⊙ . The early spectra are hot and blue with weak He i lines, and a complicated Hα region suggested to be a multicomponent feature. Modelling the spectra required ∼0.08 M⊙ of H at velocities >11 000 km s −1 and a total He mass of ∼1.0 M⊙ at velocities >9500 km s −1 above CO-rich ejecta. This model has a ratio of kinetic energy and ejected mass of 0.85$_{-0.3}^{+0.5}$  foe M⊙ −1 . The high luminosity and explosion energy results in a broadened Hα line that is blended with Si ii, C ii, and He i, which led to the initial classification of SN 2020cpg as a Type Ib. We instead classify SN 2020cpg as a bright transitional event between the Type Ib and Type IIb classes. Comparing our model parameters to stellar evolution models, a progenitor mass of 25–30 M⊙, i.e. stripped of most of the hydrogen shell and of some of the helium shell prior to collapse produces a He core of comparable mass. The excess 56 Ni production in SN 2020cpg as compared to objects of similar ejected mass may suggest evidence of additional energy sources such as a failed GRB or weak magnetar energy injection, or a smaller remnant mass.